Re-envisioning education and democracy - Kurth-Schai, Ruthanne; Green, Charles R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
The future of public education and democracy is at risk. Powerful forces are eroding commitment to public schools and weakening democratic resolve. Yet even in deeply troubling times, it is possible to broaden social imagination and empower effective advocacy for systemic progressive reform. Re-envisioning Education and Democracy explores challenges and opportunities for restructuring public education to establish and sustain more broadly inclusive, deeply democratic, and effectively transforming approaches to social inquiry and civic participation.Re-envisioning Education and Democracy adopts a non-traditional format to extend social awareness and imagination. Within each chapter, one episode of an evolving strategic narrative traces the life cycle of a systemic reform initiative. This is followed by an exploratory essay that draws from theory, research, criticism, and practice to prompt consideration of focal issues. Woven through each chapter is a poetically framed meditative stream informed by varied historical and cultural conceptions of oracles. A developmental sequence of social learning strategies (exploratory democratic practices), accompanied by thematic bibliographic references, are included to model democratic teaching and learning applicable in classroom and community settings.